Despising Our Mothers, Despising Ourselves. - Papazoglou, Orania (First Things: A Monthly Journal of Religion & Public Life, 1992)
Comments on a decline in self-respect of women of the 1990s in the U.S. Indication of an increase in the number of self-help books for women; Reason for the lack of self-respect and sense of personal dignity of women; Impact of the U.S. feminist dispensation on women of the nineties.